Diagnostic challenge of concomitant small bowel atresia and Hirschsprung's disease - I. Belbahri; G. Fusi; Thibault Planchamp T; S. Mouttalib; L. Carfagna; A. Le Mandat; O. Abbo (Elsevier, 2022)
The incidence of ileal atresia ranges from 1/5000 to 1/12000 births. The incidence of Hirschsprung's disease is 1/5000.The combination of Hirschsprung disease and ileal atresia during infancy seems to be a rare event and the exact incidence of the association of the two malformations remains unknown.Several embryo-pathological theories have been offered to explain the correlation of these two malformations. Some of them state that atresia would be a consequence of aganglionnosis and some others the contrary.The urgency of an early detection of this associations is related to her increased morbidity during management, especially if part of the phenotype remains unidentified.To date, less than 25 case of ileal atresia associated with Hirschsprung's disease are reported in Literature.We present two cases managed in our department initially for ileal atresia. Diagnosis of total colonic Hirschsprung's disease associated was placed later, after the appearance of an intestinal occlusion at the time of the restoration of digestive continuity. The first case was derived three times, and the second twice before becoming digestive self-sufficient.The dysfunction of the anastomosis after restoration of continuity is a dangerous complication which underlines the interest of the early diagnosis of the association ileal atresia and Hirschsprung's disease. It is necessary to have the rectal biopsy early, especially when the patient continues to exhibit poor bowel function after corrective surgery.